New and interesting saxicolous species of Buellia De Not. (Caliciaceae, lichenized ascomycota) from India - Ngangom, Roshinikumar; Nayaka, Sanjeeva; Mohabe, Satish; Reddy, A. Madhusudhana (Phytotaxa, 2025)
Three new saxicolous species of the lichen genus Buellia De Not. from India are described here, namely Buellia austroindica, B. subhemispherica and B. vizagensis. All the three species are characterized by an amyloid medulla and contain xanthones, connorstictic, and norstictic acid. The species B. austroindica is distinguished by its brownish yellow, rimose-areolate, UV+ pale white thallus, and orange pruina on the apothecial disc. Buellia subhemispherica is characterized by a pale grey to ivory white, rimose-areolate, UV+ orange thallus and an exciple that is aeruginose-pigmented with a paler middle layer. Buellia vizagensis is characterized by a warm white to white-grey, rimose areolate, UV+ orange thallus and yellowish brown pruina on the apothecial disc. Buellia cinnabarina and B. spuria are reported for the first time from India. Detailed descriptions, figures and distribution maps of all the species are provided.